Hubungan Kecemasan, Selft-Efficacy terhadap Hasil Belajar Kimia Farmasi - Fadli, Muhamad; Mahaly, Sawal; Kasman, Risqah A. (Universitas Negeri Padang, 2025)
The low academic achievement in pharmaceutical chemistry at the SMK level highlights the need for an in-depth examination of the psychological factors influencing student performance. This study aims to analyze the relationship between self-efficacy and anxiety with learning outcomes in pharmaceutical chemistry among 10th-grade students at SMK Negeri 3 Kesehatan dan Pekerjaan Sosial Mimika. The research employs a quantitative approach with a correlational survey design. A sample of 120 students was selected using proportionate stratified random sampling. The instruments used were self-efficacy and anxiety questionnaires, which were tested for validity and reliability, along with exam documentation for learning outcomes. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results showed that self-efficacy was positively significantly related (r = 0.598; p < 0.001), while anxiety was negatively significantly related (r = -0.463; p = 0.001) to learning outcomes. These findings emphasize the importance of enhancing self-efficacy and managing anxiety within instructional strategies